2018
DOI: 10.3390/medicines5030083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hochuekkito (Buzhongyiqitang) on Nasal Cavity Colonization of Methicillin-Resistant Staphylococcus aureus in Murine Model

Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) infections are largely preceded by colonization with MRSA. Hochuekkito is the formula composing 10 herbal medicines in traditional Kampo medicine to treat infirmity and to stimulate immune functions. We evaluated the efficacy of hochuekkito extract (HET) against MRSA colonization using a nasal infection murine model. Methods: We evaluated the effects of HET as follows: (1) the growth inhibition by measuring turbidity of bacterial culture in vitro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…HET has an effect on innate immunity as shown by increases in NK activity and cytokines. In infection models of bacterial [23,26–30] and viral infection [31–36], HET also increased cytokines. The effects on various cytokines are recognized for the whole body, notably the lung and alveoli (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HET has an effect on innate immunity as shown by increases in NK activity and cytokines. In infection models of bacterial [23,26–30] and viral infection [31–36], HET also increased cytokines. The effects on various cytokines are recognized for the whole body, notably the lung and alveoli (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of immune deficiency by age [20], steroids [21], cyclophosphamide [22], mitomycin C [23], and restraint stress [24,25], HET improved reduced immune function by both innate and acquired immunity. Related to these immuno‐stimulatory effects, HET exhibited a preventive effect from infection by Salmonella enteritidis [26], Listeria monocytogenes [27,28], Helicobacter pylori [29], methicillin‐resistant Staphylococcus aureus (MRSA) [30], influenza virus [31–35], cytomegalovirus [36], and Plasmodium chabaudi [37]. HET also exhibited a protective effect on cancer caused by inoculation of cancer cells [38,39] or carcinogenic substances [40–42].…”
Section: Pharmacological Studies On Hetmentioning
confidence: 99%
See 1 more Smart Citation
“…It was introduced to Japan along with the entirety of the Chinese culture [36] and to Korea with Buddhism in the beginning of the 6 th century [37]. Before Western culture was introduced to East Asia in 19 th century, TCM was the main medical system used to treat all types of diseases [38] with some TCM decoction formulas still in use such as Shegan Mahuang Decoction recorded in "Synopsis of Golden Chamber" for asthma [39], Bu Zhong Yi Qi Decoction (Hochuekkito) recorded in "Spleen Gastric eory" for infirmity [40][41][42], and Mahuang Decoction (Maoto) recorded in "Treatise on Fevers" for flu [43,44]. Considering that China, Hong Kong, Taiwan, Korea, and Japan share the same TCM origin and regulatory interests in TM/CM products with a long history of use, they were included in this comparative study.…”
Section: Study Targetsmentioning
confidence: 99%
“…In China, TCM (traditional Chinese medicine) has a long history in treating a variety of infectious diseases. Minami et al demonstrated that Buzhongyiqitang, which is commonly used to improve the immunity of frail elderly people, could effectively treat nasal infection of MRSA in a mouse model [10].…”
mentioning
confidence: 99%